Montelukast in Allergic Rhinitis: A Review (Medicine Today, 2013)
Leukotriene inhibitors are the first new class of medications for the treatment of persistent asthma that have been approved by the U.S food and drug Administration in more than two decades. They also have been approved for the treatment of Allergic Rhinitis. Leukotrienes are inflammatory mediators that are known as the slow-reacting substance of anaphylaxis. Synthesis of these mediators results from the cleavage of arachidonic acid in cell membranes, exert their biologic effect by binding and activating specific adaptors. This occurs in a series of events that lead to their important role in the Allergic Rhinitis. Because agents lead to the production of symptoms, the use of leukotriene inhibitors, particularly montelukast seems appropriate. These classes of drug can block the binding of leukotrienes to CysLT1 receptors and can also result in the prevention of leukotriene activity. Montelukast is the most commonly used inhibitor of the leukotriene pathway because of its ease of use , good safety profile, and once-daily regimen. We conduct a systematic review of studies that have evaluated montelikast in the treatment of Allergic Rhinitis. This review focuses on the pathophysiology and effect of montelukast in Allergic Rhinitis. The purpose of this paper is to provide an overview of the accumulation data concerning these agents in treating Allergic Rhinitis. Montelukast provides an effective and well tolerated oral treatment for Allergic Rhinitis.DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15012 Medicine Today 2012 Vol.24(2): 75-78